Introducing a simple tissue equivalent anthropomorphic phantom for radiation dosimetry in diagnostic radiology and radiotherapy - Hasanzadeh, Hadi; Abedelahi, Ali (Archives of Advances in Biosciences, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> It is important to measure organ dose in diagnostic radiology & radiotherapy. Because measurement on patients has some limitations, phantoms are being constructed to be implemented. One kind of several phantoms which is being used so far is anthropomorphic phantom which is similar to a man. In this work, using human natural bone as phantom skeletal tissue & paraffin plus NaCl (as impurity) as soft tissue substitute an anthropomorphic phantom was constructed which consists of three parts: 1. head & neck 2.torso 3.hip. Phantom dimensions were selected from the standard man. To measure absorbed dose in tissues, at the sites of parotid, thyroid, sternum, diaphragm, abdomen and hip some cylinders were inserted which were constructed from phantom material and had some cavities to insert TLDs in different depths. Due to importance of photoelectric effect in diagnostic radiology & Compton effect in radiotherapy, two important parameters which should be considered in construction of a phantom is effective atomic number and electronic density were6.57& 3.36×1023 electron.gr-1 , respectively.